Dabigatran-induced nephropathy and its successful treatment with Idarucizumab - case report and literature review. Issue 169 (September 2018) - Awesat, Jenan; Sagy, Iftach; Haviv, Yosef S.; Rabinovich, Anat; Jotkowitz, Alan; Shleyfer, Elena; Barski, Leonid
Abstract: Background: Anticoagulant induced renal injury has been previously described with Warfarin treatment. In the last decade direct oral anticoagulants (DOAC) were introduced. They include direct inhibitors of factor Xa (Rivaroxaban, Apixaban, Edoxaban) and a thrombin inhibitor (Dabigatran). There are isolated reports describing acute kidney injury (AKI) due to the use of DOACs. Case report: We report a clinical case of an 80-year-old patient recently started on Dabigatran for new onset atrial fibrillation. She presented with AKI and hematuria, urine specimen showed RBC casts, and a working diagnosis of anticoagulant nephropathy due to Dabigatran was made. During hospitalization she was treated with Idarucizumab with a full recovery of renal function. To the best of our knowledge, there are 4 published case reports describing kidney injury produced by Dabigatran. Conclusion: The use of DOACs is increasing rapidly, with increasing concern about its safety profile and, in particular, its potential harmful effect on renal function. As described in our case, treatment with Praxbind for Dabigatran induced kidney injury may be an acceptable management strategy that may obviate the need for urgent dialysis in selected cases by complete reversal of the AKI. Highlights: There are isolated reports describing acute kidney injury (AKI) due to the use of direct oral anticoagulants (DOACs). Clinical case of an 80-year-old patient recently started on Dabigatran presented with AKI and hematuria. AKI was treated with Idarucizumab with full recovery of renal function. Treatment with Idarucizumab for dabigatran induced kidney injury may be an acceptable management strategy.